Pengaruh Earnings Management Dan GCG Terhadap Tax Avoidance Pada Perusahaan Consumer Cyclical Dan Non Cyclical Yang Terdapat Di Bei Tahun 2020-2022 - Maharani, Siti Artika; Putri, Ade Hanifa (Media Bisnis, 2024)
The purpose of this research is to analyze the effect of earnings management, independent commissioner, audit quality, audit committee, sales growth, and capital intensity on tax avoidance at companies listed on the Indonesia Stock Exchange, especially in the Consumer Cyclical and Non Cyclical from 2020 to 2022, particularly in Consumer Cyclical and Non-Cyclical sectors from 2020 to 2022. Samples are obtained through purposive sampling method, which only 62 companies that met the sampling criteria for the research. The research used multiple regression method to test the effect of each variable in influencing tax avoidance. The result of this research indicates that sales growth and capital intensity have an effect on tax avoidance. while, earnings management, independent commissioners, audit quality, and audit committee have no effect on tax avoidance.